1980
DOI: 10.1137/0209064
|View full text |Cite
|
Sign up to set email alerts
|

Orthogonal Packings in Two Dimensions

Abstract: Abstract. We consider problems of packing an arbitrary collection of rectangular pieces into an open-ended, rectangular bin so as to minimize the height achieved by any piece. This problem has numerous applications in operations research and studies of computer operation. We devise efficient approximation algorithms, study their limitations, and derive worst-case bounds on the performance of the packings they produce.Key words, two-dimensional packing, bin packing, resource constrained scheduling 1. Introducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
334
0
16

Year Published

2005
2005
2021
2021

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 585 publications
(352 citation statements)
references
References 7 publications
(5 reference statements)
2
334
0
16
Order By: Relevance
“…The LSF has been shown to be a 3-approximation [2]. Some results about asymptotic performance ratio of different strategies for this problem and improvements are presented in [1,4,5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The LSF has been shown to be a 3-approximation [2]. Some results about asymptotic performance ratio of different strategies for this problem and improvements are presented in [1,4,5].…”
Section: Discussionmentioning
confidence: 99%
“…Before the time t c the kth node is filled at least half (the property of the BLD algorithm) [2], hence …”
Section: Mct-a-lsf Theorem 2 For Any List Of Rigid Jobs and Any Set mentioning
confidence: 99%
“…The basic idea is to select, in a first step, an allocation (the number of processors allocated to each task) and then solve the resulting non-moldable scheduling problem, which is a classical multiprocessor scheduling problem. As far as the makespan criterion is concerned, this problem is identical to a 2-dimensional strip-packing problem [1,4]. It is clear that applying an approximation of guarantee λ for the non-moldable problem on the allocation of an optimal solution provides the same guarantee λ for the moldable problem.…”
Section: Related Workmentioning
confidence: 99%
“…Based on this permutation representation, several greedy placement heuristics have been investigated for the 2D-SPP. BLF (Bottom Left Fill) is such a heuristic [27]. Basically, BLF places each object at the left-most and lowest possible free area.…”
Section: Search Space: a Direct Representationmentioning
confidence: 99%
“…In local search algorithms, the initial solution s 0 specifies where the search begins in S. TSD uses the BLF procedure [27] to construct s 0 , where the π permutation orders the r i ∈ R first by decreasing width, and, second, by decreasing height if necessary (randomly last). We employed this decoder / order since previous experiments suggested that the BLF placement algorithm usually outperforms other φ decoders, see [28,31] for instance.…”
Section: Initial Solutionmentioning
confidence: 99%